(untitled) (JURNAL ADMINISTRASI BISNIS, 2019)
This study was conducted to determine whether there is an effect of compensation on employee performance at PT. PLN (Persero) UP3 Manado. Human resources play an important role in every company, because of that the company must be able to improve performance in the company by providing compensation in accordance with its achievements. This research is a quantitative approach because this research is presented with numbers, starting from data collection, interpretation of the data, and the appearance of the results. In this study, the population studied was 60 employees. Based on the results of a simple linear regression analysis concluded that compensation affects the performance of employees of PT. PLN (Persero) UP3 Manado. This is evidenced by the results of the hypothesis test (t-test).